Prognostic Role of Catecholamine in Moderate-to-Severe Traumatic Brain Injury: A Prospective Observational Cohort Study - Singh, Anamika; Prajapati, Hanuman Prasad; Kumar, Raj; Singh, Naresh Pal; Kumar, Ajai (Asian Journal of Neurosurgery, 2022)
Objective Traumatic brain injury leads to the activation of sympathetic nervous system and elevation in serum catecholamine levels. The aim of this study was to determine whether catecholamine level obtained within 24 hours of traumatic brain injury provides a reliable prognostic marker for outcome.Materials and Methods This study was a prospective observational cohort study on 36 moderate-to-severe traumatic brain injury. Plasma epinephrine (E), norepinephrine (NE), and dopamine (DA) levels were measured by using computed tomography enzyme-linked immunosorbent assay test and compared with Glasgow coma scale (GCS) that was obtained concurrently. Neurological outcome was determined by GCS at day 7 of treatment and by Glasgow outcome scale at mean follow-up of 9.73 ± 2.26 months.Results Patients with GCS 3 to 4 had markedly increase in baseline mean E (771.5 ± 126.0), NE (2,225.0 ± 215.4), and DA (590.2 ± 38.8) levels as compared with control, while patients with better GCS (11–12) had mildly elevated levels. Patients with GCS 5 to 10 had intermediate values. Cases with markedly elevated baseline E, NE, and DA level were either died or remained in poor GCS (3 or 4) at day 7 of treatment and remained in persistent vegetative state at mean follow-up of 9.73 ± 2.26 months. Cases with only mildly elevated E, NE, and DA level were improved to better GCS on treatment and had good recovery on follow-up.Conclusion These data indicate that a markedly elevated catecholamine level was an excellent endogenous and readily quantifiable marker that appears to reflect the extent of brain injury and predict the likelihood of recovery.
Keywords: traumatic brain injury; moderate-to-severe; catecholamine; Glasgow coma scale; outcomes